1979
DOI: 10.1111/j.1365-2133.1979.tb15102.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation analysis of trace elements in skin.

Abstract: SUMMARY Selenium(Se) has been determined in skin by neutron activation analysis applying selective irradiation and cooling time, followed by measurement of the activity on a high resolution germanium lithium (Ge(Li)) detector. The levels and distribution of Se in normal abdominal and plantar skin, together with other available evidence, lead us to believe that it is an essential trace element in man. It is suggested that Se has an essential role in skin keratinization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The normal adult human body contains about 1 mg silver, 21 and the smallest amount of silver reported to produce generalized argyria in humans ranges from 4 to 5 g to 20–40 g 4 ,. 23 The amount of silver in the full‐thickness skin of patients with argyria, as assessed by neutron activation analysis, was estimated to be more than 80 24 –100 times 25 that in normal control skin. Another neutron activation study estimated the total body silver content in a patient with generalized argyria to be as high as 8000 times the normal value 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The normal adult human body contains about 1 mg silver, 21 and the smallest amount of silver reported to produce generalized argyria in humans ranges from 4 to 5 g to 20–40 g 4 ,. 23 The amount of silver in the full‐thickness skin of patients with argyria, as assessed by neutron activation analysis, was estimated to be more than 80 24 –100 times 25 that in normal control skin. Another neutron activation study estimated the total body silver content in a patient with generalized argyria to be as high as 8000 times the normal value 26 .…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the epidermal:dermal ratio of Se is much lower than for Zn, Cu or Mn and varies between 0•8 and 1•5 in abdominal skin. As for other nutrients with antioxidant properties, this ratio depends on skin site and is much lower in plantar skin (Molokhia et al 1979). Such a distribution is likely to be influenced by the type of environmental insult faced by skin on different parts of the body.…”
Section: Seleniummentioning
confidence: 99%
“…The whole body of an adult contains 1.4-2.3 grams of zinc, with an average zinc level of 2.5 μgm/ml in the whole blood or 2.7 μgm/ml in plasma 3 .…”
Section: Introductionmentioning
confidence: 99%